2006
DOI: 10.1248/yakushi.126.1377
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Benidipine in a Rat Model of Experimental Angina

Abstract: To compare the antianginal eŠects of 1,4-dihydropyridine-type calcium-channel blockers, we evaluated the eŠects of benidipine, amlodipine, nifedipine, and efonidipine on vasopressin-induced myocardial ischemia in rats, an experimental model of angina. Intravenous administration of benidipine (3 mg/kg), amlodipine (1000 mg/kg), and nifedipine (100 mg/kg) suppressed the vasopressin-induced S-wave depression, an index of myocardial ischemia. Efonidipine (100 mg/kg, i.v.) tended to inhibit the S-wave depression. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Nifedipine CR was effective in maintaining higher effective blood concentrations for more than 12 h when the administration timing was changed to after the evening meal. However, benidipine, a dihydropyridine Ca channel blocker, the same as nifedipine, has been reported to have coronary dilatation action and sustained action better than those of nifedipine in pharmacological research using various ischemic heart disease models [34,35]. The approved dosage and administration of benidipine for angina pectoris is 4 mg twice a day [22].…”
Section: Discussionmentioning
confidence: 99%
“…Nifedipine CR was effective in maintaining higher effective blood concentrations for more than 12 h when the administration timing was changed to after the evening meal. However, benidipine, a dihydropyridine Ca channel blocker, the same as nifedipine, has been reported to have coronary dilatation action and sustained action better than those of nifedipine in pharmacological research using various ischemic heart disease models [34,35]. The approved dosage and administration of benidipine for angina pectoris is 4 mg twice a day [22].…”
Section: Discussionmentioning
confidence: 99%
“…Following vasopressin administration, the ECG alterations (ST segment elevation) were taken into consideration as a metric to show the presence of myocardial ischemia, which may be caused by coronary vasoconstriction [ 55 ]. ST segment elevation was defined as the difference in ST segment amplitude following and immediately before vasopressin delivery [ 56 ]. Four groups of six male Sprague-Dawley rats, each weighing 250–300 g, were used.…”
Section: Methodsmentioning
confidence: 99%
“…cannula, vasopressin (VP) was intravenously injected at a dosage of 2 IU/kg through the same cannula. The ST-segment depression ⩾ 1 μv was considered as an index of myocardial angina (Ikeda et al, 2006), as shown in which recorded by the Powerlab system (Model Figure). The recorded signals should be free of electrical interference and noise.…”
Section: Methodsmentioning
confidence: 99%